Os sistemas financeiros e a evolução das regras de supervisão bancária - Silva, Helom Oliveira da (2010)
Financial systems are today one of the most heavily regulated sectors of the world and whose role has been widely discussed in the economic debate, considering the route of infection they pose to the economy, as presented in the recent international financial crisis. Thus, this study aimed at reviewing the theoretical framework pertaining to the economic theories of regulation, the role of financial systems in the economy and the rationale for state intervention in these markets, as well as changes the rules on supervision of the sector financial. It also presented a brief discussion of the international financial crisis and the new role of emerging economies in global economic scenario.